Assessment of antibiotic storage practices, knowledge, and awareness related to antibiotic uses and antibiotic resistance among household members in post-conflict areas of Pakistan: Bi-central study - Khan, Faiz Ullah; Mallhi, Tauqeer Hussain; Khan, Qasim; Khan, Farman Ullah; Hayat, Khezar; Khan, Yusra Habib; Ahmad, Tawseef; Fang, Yu (Frontiers in Medicine, 2022)
Background The storage of antimicrobials at home is frequently in-practice in various developing countries, resulting an irrational use, antibiotic resistance, and toxicities. This condition may worsen more in conflict zones where health facilities are limited. This study aimed to determine the storage and use of leftover antibiotics among households (HHs) along with knowledge and awareness about antibiotics and antibiotic resistance (ABR). Methods A descriptive cross-sectional study design was employed. Members of HHs were invited to participate in the survey while using a convenient sampling technique. The data were obtained using a validated questionnaire and analyzed through SPSS. Results A total of 96 HHs were randomly selected from two districts (n = 50, n = 46), with most of the participants being men between the ages of 18 and 28 (n = 45, 46.9%) years. The majority of HHs (n = 32, 33.3%) had six to eight total family members, with one to two chronic diseases (n = 63, 65.6%), individual families (n = 60, 62.5%), and with (n = 35, 36.5%) LRTIs (lower respiratory tract infections). The HHs were aware of the word “antibiotic” (n = 59, 61.5%) and gave correct replies to amoxicillin as an antibiotic (n = 42, 43.8%); on the other hand, HHs also thought of paracetamol as an antibiotic (n = 45, 47.9%). They identified the most common brands of antibiotics easily, and a majority of them (n = 69, 71.9%) had never heard of ABR before and had lower levels of awareness. The most stored antibiotic at home (n=38, 39.6%) was azithromycin (J01FA10). In addition, they had multiple needless (1–2, n = 62, 64.6%; 3–4, n = 29, 30.2%) and antibiotics in their houses. Age had a strong association (p = 0.017, H = 12) affected the mean knowledge scores related to antibiotic use. Association of education levels (p = 0.001, H = 52.8) and occupation (p = 0.04, H = 10) with proper antibiotics use were found to be significant. However, family members with more than one chronic illness (p = 0.09, H = 0.8) showed a significant relationship with their awareness of antibiotics. Conclusion Participants generally stored various antibiotics of different classes in their homes. Lack of knowledge related to the appropriate usage of antibiotics, use of leftover antibiotics, and awareness related to ABR were unknown to the participants.